Pengaruh Kompetensi Guru, Motivasi dan Lingkungan Kerja terhadap Kinerja Guru pada SMP Kartika 1-2 Medan - Nina Gusmalia; Sjahril Effendy; Muis Fauzi Rambe (Jurnal AKMAMI (Akuntansi Manajemen Ekonomi), 2021)
This study aims to determine how much influence teacher competence, motivation, and work environment have on teacher performance at SMP Kartika 1-2 Medan. The results showed that simultaneously teacher competence, motivation and work environment had a significant effect on teacher performance at SMP Kartika 1-2 Medan. Partially teacher competence, motivation and work environment have a significant effect on teacher performance at SMP Kartika 1-2 Medan and partially teacher competence, work motivation and work environment have a significant effect on teacher performance at SMP Kartika 1-2 Medan.